A Study on the Regulation of TRPM8 Signaling Pathway by Interior-warming Medicines in Traditional Chinese Medicine - Wei, Yuanjun; Xiong, Chengcheng; Zhan, Yanran; Fu, Jiangbo; Yang, Chaoyan; Chen, Yanfen (Current Traditional Medicine, 2026)
BackgroundInterior-warming medicines (Wēnlǐ herbs) have the effect of warming the interior of the body and dispelling cold, and they are traditionally used for interior cold syndrome. Currently, they are used for treating gastrointestinal disorders, rheumatoid arthritis, tumors, etc. Transient receptor potential channel M8 (TRPM8) is a non-selective cation channel that can be activated by low temperature and menthol. However, the mechanism of temperature regulation of interior-warming medicines is not clear. This study designed an in vitro experiment on the TRPM8 signaling pathway using interior-warming medicines, aiming to investigate the relationship between the hot property of interior-warming medicines and the regulatory effect of TRPM8.MethodsThe breast cancer cell line 7 was cultured at different temperatures as a research model, six kinds of interior-warming medicines were used, and a medicated serum from rats was prepared as a test drug. PCR and western blotting were carried out to investigate their effects on TRPM8 mRNA and protein expression. ELISA and flow cytometry were conducted to detect intracellular cAMP and Ca2+ concentration.ResultsCompared with the blank-containing serum group, interior-warming medicines had no significant effect on the expression of TRPM8 at 37°C, while they could inhibit the expression of TRPM8 at low temperatures (30°C). Moreover, the six herbs could increase intracellular cAMP content and reduce Ca2+ concentration at different temperatures.DiscussionTRPM8 plays an important role in temperature sensation, pain, inflammation and tumorigenesis, while generates specific calcium ion influx under low-temperature stimulation. This study showed that six interior-warming medicines down-regulated TRPM8 expression, especially at low temperatures, and they regulated intracellular Ca2+ release in addition to Ca2+ influx.ConclusionThe natural hot property of interior-warming medicines may be associated with the regulation of the TRPM8 signaling pathway, causing Ca2+ influx blocking, which provides a deeper experimental basis for their clinical application and new drug development.
Keywords: Interior-warming medicines (Wēnlǐ herbs)